Pengaruh Atribut dan Layanan dalam Membentuk Kepercayaan dan Keputusan Berkunjung ke Agrowisata Subak Jatiluwih Tabanan: Pengaruh Atribut dan Layanan dalam Membentuk Kepercayaan dan Keputusan Berkunjung ke Agrowisata Subak Jatiluwih Tabanan - Oktaryanti, Ni Made Nita Dwi; Sukendar, Ni Made Classia (Universitas Duta Bangsa Surakarta, 2025)
Jatiluwih Subak Agrotourism is known for its stunning natural panorama, especially its unique terraced rice fields and traditional irrigation system which has been recognized as a UNESCO World Cultural Heritage. This study aims to examine the influence between variables, namely: (a) attributes on tourists' trust and visiting decisions; (b) service quality on trust and visiting decisions; (c) trust on visiting decisions; (d) the role of trust as a mediating variable in the relationship between attributes and visiting decisions; and (e) the role of trust as a mediating variable in the relationship between services and visiting decisions. The approach used is qualitative and quantitative with a survey method by distributing questionnaires to 100 tourist respondents who visited Jatiluwih Subak Agrotourism. Data analysis was carried out using Structural Equation Modeling (SEM) using SmartPLS 4.1 software. The results of the study show that: (a) attributes have a positive and significant effect on trust; (b) services have a positive and significant effect on trust; (c) attributes have a positive and significant effect on visiting decisions; (d) services have a positive and significant effect on visiting decisions; (e) trust has a positive and significant influence on the decision to visit; (f) attributes are not proven to have a significant influence on the decision to visit through trust as a mediating variable; and (g) service has a significant influence on the decision to visit with trust as a mediating variable. Suggestions that can be given to managers include arranging parking areas, conducting routine evaluations, and providing consistency in services to maintain tourists' trust and decisions.